Strategi Pemasaran Toko Kasih Sayang Jaya Blok B dalam Mempertahankan Jumlah Pelanggan (Di Tinjau Dari Perspektif Ekonomi Islam) - Khairani, Indah (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2024)
Purpose – This research aims to find out 1) the marketing strategy of Toko Kasih Sayang Jaya Blok B in maintaining the number of customers from an Islamic economic perspective. 2) To find out the obstacles faced by the Kasih Sayang Jaya Blok B Store in maintaining the number of customers. Method – The research method used is a qualitative approach. This type of research is field research. Field research is research using informants or respondents through data collection instruments such as interviews, observation and documentation. Results – The research results show that it can be concluded that: Product Strategy, namely providing various types of hijabs, maintaining the best quality, and providing friendly service to consumers, Pricing strategy, namely in setting prices that have been considered according to quality, market conditions, not taking excessive profits and also provide discounts to consumers, Location Strategy, namely the location of the Kasih Sayang Jaya shop is in the center of Langsa city, but the shop is in an alley. Promotion, the compassion jaya store never launches advertising messages to influence the consumer audience. Kasih Sayang Jaya Store has succeeded in combining Islamic economic principles in its marketing strategy. A fair attitude, good personality, humble service, and orientation towards mutual prosperity are the basis for running a business in marketing, creating a positive relationship between the shop and its consumers. The Kasih Sayang Jaya Store faced problems during the surge in demand for Ramadan and Eid with difficulty in getting high quality stock. Challenges involve capital constraints, competition, and price.